Bound-Free Collective Electron Excitation in Negatively Charged Metal Clusters - Tiggesbäumker, Josef; Köller, Lars; Meiwes-Broer, Karl-Heinz (Chemical Physics Letters)
We report measurements of the photodestruction cross sections of small sputtered negatively charged silver clusters (AgN−, 5 ≤ N ≤ 19). Resonance-like peaks are observed in the optical spectra which can be attributed to collective electron excitations. In contrast to neutral and positively charged clusters, the resonance energies are far above the electron emission threshold. With decreasing cluster size the resonance positions distinctly shift towards lower energies. This red-shift is explained by an extension of a semi-empirical model by Liebsch which we previously used to interpret the blue-shift in AgN+ [J. Tiggesbäumker, L. Köller, K.H. Meiwes-Broer and A. Liebsch, Phys. Rev. A 48 (1993) R1749], now including the polarizabilities of small metal clusters.